Kebutuhan Spiritual dan Pemenuhan Spiritual Pasien COVID-19 - Sherly Manurung; Henny Suzana Mediani; Aan Nuraeni (Institut Penelitian Matematika, Komputer, Keperawatan, Pendidikan dan Ekonomi (IPM2KPE), 2022)
This study aims to determine spiritual needs, fulfill spiritual needs and examine problems or obstacles from health workers in meeting the spiritual needs of COVID-19 patients. The method used is a literature review by browsing articles on the Pubmed, SAGE and Google Scholar databases. The results showed that the spiritual needs of COVID-19 patients increased along with the illness they experienced. Spiritual support is provided by all health professionals, from nurses, doctors and other health workers, with prayer, singing and statements of support that are carried out at the bedside and virtually. The obstacles that often arise are the lack of health workers and their understanding of meeting the spiritual needs of patients. In conclusion, all health professionals can carry spiritual needs such as prayer, singing and statements of support. Barriers often faced in patients' spiritual fulfillment are the number of health workers and the lack of understanding of spiritual concepts from health workers. Keywords: Spiritual Needs, COVID-19 Patients, Spiritual Care